Analysis of Practicum-Based Cooperative Learning Outcomes on Student's Cognitive Learning Outcomes - Oktafianti, Alfi Ainun; Nafisa, El Saffa (APPLICATION: Applied science in Learning Research, 2023)
This research aims to analyze the results of practicum-based cooperative learning on students' cognitive learning outcomes. The background of this research is that creating quality education does not only focus on mastering subject matter, but also on developing skills such as critical thinking, creative, communicative and collaborative. One strategy that has been proven effective is practicum-based cooperative learning. This approach emphasizes the active involvement of students. This research uses a qualitative approach with a descriptive type. The research location is at the Superior MA K.H. ABD. Wahab Hasbulloh. Data sources are divided into two, namely primary and secondary. The primary data source is class XI MIPA students with a total of 50 students and the secondary data source is the results of observation and documentation. Data collection techniques through interviews, observation and documentation through practical activities in making excretory system props. Data analysis techniques use data presentation and drawing conclusions. The research results show 1) Practicum-based cooperative learning is effective in improving students' cognitive learning outcomes, 2) Group collaboration in practicum helps students understand concepts more deeply and increases learning motivation, 3) This approach develops 21st century skills such as thinking critical, creative, communicative and collaborative.